Old and New Cultivars of Soya Bean (Glycine max L.) Subjected to Soil Drying Differ in Abscisic Acid Accumulation, Water Relations Characteristics and Yield. (21st July 2015) - He, J.; Du, Y.‐L.; Wang, T.; Turner, N. C.; Xi, Y.; Li, F.‐M.
Abstract: Two old (Huangsedadou and Longxixiaohuangpi (LX)) and two new (Jindou 19 (JD) and Zhonghuang 30 (ZH)) soya bean ( Glycine max (L.) Merr.) cultivars were used to investigate the influence of soil drying on the abscisic acid (ABA) accumulation in leaves, stomatal conductance ( g s ), leaf water relations, osmotic adjustment (OA), leaf desiccation tolerance, yield and yield components. The greater ABA accumulation was induced by soil drying, which also inducing g s decreased at higher soil water contents (SWC) and leaf relative water content (RWC) significantly decreased at lower SWC in the new soya bean cultivars than in the old soya bean cultivars. The soil water threshold between the value at which stomata began to close and the RWC began to decrease was significantly broader in the new cultivars than in the old cultivars. The new cultivars had significantly higher OA and lower lethal leaf water potential than old cultivars when the soil dried. The old cultivars had greater biomass, but lower grain yield than the new cultivars in well‐watered, moderate stress and severe stress conditions. Thus with soil drying, the new soya bean cultivars demonstrated greater adaptation to drought by inducing greater ABA accumulation, stomatal closure at higher SWC, enhanced OA and better water relations, associated with increased leaf desiccation tolerance, greater water use efficiency and higher yield.